Evaluating spatiotemporal variations and exposure risk of ground-level ozone concentrations across China from 2000 to 2020 using high-resolution satellite-derived data - Q. He; Q. He; J. Cao; P. E. Saide; P. E. Saide; T. Ye; W. Wang; M. Zhang; J. Huang (Atmospheric Chemistry and Physics, 2025)
Understanding the spatial and temporal characteristics of both long- and short-term exposure to ground-level ozone is crucial for refining environmental management and improving health studies. However, such studies have been constrained by the availability of high-resolution spatiotemporal data. To address this gap, we characterized ground-level ozone variations and exposure risks across multiple spatial (pixel, county, region, and national) and temporal (daily, monthly, seasonal, and annual) scales using daily 1 km ozone data from 2000 to 2020, derived from satellite-sourced land surface temperature data via a machine-learning hindcast method. The model provided reliable estimates, validated through rigorous cross-validation and direct comparison with external ground-level ozone measurements. Our long-term estimates revealed seasonal shifts in high-exposure ozone centers: spring in eastern China, summer in the North China Plain (NCP), and autumn in the Pearl River Delta (PRD). A non-monotonic trend was observed, with ozone levels rising from 2001–2007 at a rate of 0.47 µg<mspace width="0.125em" linebreak="nobreak"/>m-3<mspace width="0.125em" linebreak="nobreak"/>yr-1<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="56pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="3248dee9e92a312ababaf9ec5df15514"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-6663-2025-ie00001.svg" width="56pt" height="15pt" src="acp-25-6663-2025-ie00001.png"/></svg:svg>, declining after 2008 (−0.58 µg<mspace linebreak="nobreak" width="0.125em"/>m-3<mspace width="0.125em" linebreak="nobreak"/>yr-1<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="56pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="e71bd7c8d176aa4bcf9ea4cb4628444f"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-6663-2025-ie00002.svg" width="56pt" height="15pt" src="acp-25-6663-2025-ie00002.png"/></svg:svg>), and increasing significantly from 2016–2020 (1.16 µg<mspace width="0.125em" linebreak="nobreak"/>m-3<mspace linebreak="nobreak" width="0.125em"/>yr-1<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="56pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="908934977e50a92e8745df96395eb471"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-6663-2025-ie00003.svg" width="56pt" height="15pt" src="acp-25-6663-2025-ie00003.png"/></svg:svg>), accompanied by regional and seasonal fluctuations. Notably, ozone levels increased by 0.63 µg<mspace linebreak="nobreak" width="0.125em"/>m-3<mspace width="0.125em" linebreak="nobreak"/>yr-1<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="56pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="711395868847428019be9bfaaf6430ce"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-6663-2025-ie00004.svg" width="56pt" height="15pt" src="acp-25-6663-2025-ie00004.png"/></svg:svg> in summer in the NCP during the second phase and by 6.38 µg<mspace width="0.125em" linebreak="nobreak"/>m-3<mspace width="0.125em" linebreak="nobreak"/>yr-1<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="56pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="2d16452fbd937b6c3a6756fb08c4e63e"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-6663-2025-ie00005.svg" width="56pt" height="15pt" src="acp-25-6663-2025-ie00005.png"/></svg:svg> in autumn in the PRD during the third phase. Exposure levels over 100 µg m−3 have shifted from June to May, and levels exceeding 160 µg m−3 were primarily seen in the NCP, showing an expanding trend. Our day-to-day analysis highlights the influence of meteorological factors on extreme events. These findings emphasize the need for increased public health awareness and stronger mitigation efforts.